Teachers’ attitudes and self-efficacy toward augmented reality in chemistry education - Ripsam, Melanie; Nerdel, Claudia (Frontiers in Education, 2024)
Digital media have played a central role in everyday school life, at least since the governments in various competence frameworks define the digital competence areas. With a view to experimentation in STEM lessons, digital media offers a variety of opportunities to promote learning processes. A benefit is expected from technological progress when visually imperceptible scientific processes are made visible technologies. AR combines the real and virtual worlds so that the viewer physically moves in a real environment that contains virtual elements. Consequently, AR offers good conditions for expanding students' subject-specific knowledge regarding substance-particle concept understanding. When a technology like AR is used in the classroom, the learning environment must be accepted by teachers. Teachers are actively involved in the modification of digital learning environments so that they can identify, evaluate, and select digital resources. Teachers’ acceptance, therefore, presupposes an upbeat assessment of the usability of the innovation. Attitudes and self-efficacy can influence digital literacy and, thus, acceptance. The study investigates whether chemistry teachers positively embrace AR and accept them. Considering the T(D)Pack model, the teachers' digital competencies are examined concerning the subject- and media-didactic evaluation of digital media. Self-efficacy and attitudes of teachers (N=157) are assessed. After processing the (non-/HMD-)AR-App, an acceptance and usability test (N=122) follows. The data analysis provides reliability and correlation analyses according to classical test theory. The results demonstrated that teachers saw great potential in using innovations and positively evaluated the AR learning environment on the tablet. The analyses revealed significant correlations between attitudes and acceptance.